Clinical Pharmacology Studies Supporting Oligonucleotide Therapy Development: An Assessment of Therapies Approved and in Development Between 2012 and 2018 - Hobart Rogers; Oluseyi Adeniyi; Anuradha Ramamoorthy; Samantha Bailey; Michael Pacanowski (Wiley, 2021)
Synthetic nucleotides that utilize RNA‐centric pharmacology can target diseases at the RNA level, thus altering protein expression in ways previously inaccessible to small molecules and therapeutic biologics. Recognizing that the unique pharmacology of oligonucleotides may require specific considerations in pre‐approval assessment, clinical and nonclinical pharmacology studies being conducted for a selected set of oligonucleotide therapies in a 6‐year period were assessed. This investigation focused primarily on the four following areas: (i) drug‐drug interaction (DDI) potential, (ii) organ impairment (i.e., renal and hepatic impairment), (iii) immunogenicity, and (iv) cardiac safety. Data were summarized and assessed from 14 Investigational New Drug programs and 7 New Drug Applications submitted to the US Food and Drug Administration (FDA) from the period of January 2012 to August 2018, encompassing 152 unique studies. The assessment of DDI potential was largely consistent with the recommendations of current DDI‐relevant guidances. Limited data were available to provide recommendations across organ impairment categories. Limited data on immunogenicity indicate impact on pharmacokinetic, the impact on safety and efficacy, although not extensively evaluated, appeared negligible. Cardiac safety evaluation indicated a potential for discordant translation of risk from nonclinical studies to clinical findings. Continued experience with synthetic oligonucleotide therapies will help inform the development of best practices to support their development and regulatory approval.